A phase I/Ib trial targeting the Pi3k/Akt pathway using perifosine: Long‐term progression‐free survival of patients with resistant neuroblastoma. Issue 2 (30th September 2016) - Kushner, Brian H.; Cheung, Nai‐Kong V.; Modak, Shakeel; Becher, Oren J.; Basu, Ellen M.; Roberts, Stephen S.; Kramer, Kim; Dunkel, Ira J.
Abstract : AKT plays a pivotal role in driving the malignant phenotype of many cancers, including high‐risk neuroblastoma (HR‐NB). AKT signaling, however, is active in normal tissues, raising concern about excessive toxicity from its suppression. The oral AKT inhibitor perifosine showed tolerable toxicity in adults and in our phase I trial in children with solid tumors (clinicaltrials.gov NCT00776867). We now report on the HR‐NB experience. HR‐NB patients received perifosine 50–75 mg m −2  day −1 after a loading dose of 100–200 mg m −2 on day 1, and continued on study until progressive disease. The 27 HR‐NB patients included three treated for primary refractory disease and 24 with disease resistant to salvage therapy after 1–5 (median 2) relapses; only one had MYCN ‐amplified HR‐NB. Pharmacokinetic studies showed μM concentrations consistent with cytotoxic levels in preclinical models. Nine patients (all MYCN ‐non‐amplified) remained progression‐free through 43+ to 74+ (median 54+) months from study entry, including the sole patient to show a complete response and eight patients who had persistence of abnormal 123 I‐metaiodobenzylguanidine skeletal uptake but never developed progressive disease. Toxicity was negligible in all 27 patients, even with the prolonged treatment (11–62 months, median 38) in the nine long‐term progression‐free survivors. The clinical findings ( i ) confirm the safety of therapeutic serum levels of an AKT inhibitor in children; ( ii ) support perifosine for MYCN ‐non‐amplified HR‐NB as monotherapy after completion of standard treatment or combined with other agents (based on preclinical studies) to maximize antitumor effects; and ( iii ) highlight the welcome possibility that refractory or relapsed MYCN ‐non‐amplified HR‐NB is potentially curable. Abstract : What's new? The PI3K/AKT pathway plays a crucial role in many cancers, including high‐risk neuroblastoma (HR‐NB). In this clinical study, the authors tested the AKT inhibitor perifosine in a group of pediatric patients with refractory or treatment‐resistant HR‐NB. After more than 3 years, 33% of the patients (9/27) remain progression‐free. Toxicity was negligible, alleviating concerns that suppressing the PI3K/AKT pathway might be harmful. These results suggest that refractory/relapsed NB is curable, and indicate that perifosine may provide a valuable treatment option, alone or in combination with other therapies.